2014
DOI: 10.15517/rbt.v62i2.8501
|View full text |Cite
|
Sign up to set email alerts
|

Variaciones en la historia de vida de Anadara tuberculosa (Mollusca: Bivalvia) en el ecosistema de manglar de la costa Sur de Ecuador

Abstract: Anadara tuberculosa is one of the most important bivalves along the Western Pacific coast because of its commercial value. Nevertheless, the variability in growth, long-life span, natural mortality and reproductive parameters of this mangrove cockle has not yet been described. The aim of this study was to analyze these lifehistory traits in three areas of the Southern coast of Ecuador. Empirical and length-based methods were used to estimate these biological parameters. Body size data were collected from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
3
1
2
Order By: Relevance
“…The growth of A. tuberculosa in Estero Las Lajitas was constant, reaching an estimated maximum asymptotic length similar to that estimated by Félix-Pico et al [15] on Mexican coasts; however, this value was lower than those found in studies carried out in areas influenced by the tropical-equatorial zone, where sizes of L∞ between 63 and 93 mm have been reported [12,27,29,39,40]. However, the growth estimates made in the aforementioned area were derived using the VBGM via statistical programs such as ELEFAN I [41] and FiSAT [42], and this is not the best model for describing the information generated in the present research.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The growth of A. tuberculosa in Estero Las Lajitas was constant, reaching an estimated maximum asymptotic length similar to that estimated by Félix-Pico et al [15] on Mexican coasts; however, this value was lower than those found in studies carried out in areas influenced by the tropical-equatorial zone, where sizes of L∞ between 63 and 93 mm have been reported [12,27,29,39,40]. However, the growth estimates made in the aforementioned area were derived using the VBGM via statistical programs such as ELEFAN I [41] and FiSAT [42], and this is not the best model for describing the information generated in the present research.…”
Section: Discussionsupporting
confidence: 76%
“…In this context, Panta-Vélez et al [14] mentioned that the protandry hermaphroditism of the species may be associated with the imbalance in sexual proportion, since the reproductive activity of A. tuberculosa as regards sexual maturity is not coherent with that measured in other areas of the Ecuadorian Pacific. In addition, the emergence of protandry hermaphroditism and changes in sex ratio indicate that the population may respond to anthropogenic and environmental pressures [5,12]. The numerical superiority between females and males may also be caused by the physicochemical properties of the water, which favor the development of females or interfere with the development of males, as mentioned by Guilbert [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el Ecuador su reproducción parece tener un período de máxima actividad gonadal durante el período noviembre-febrero (Ayala et al, 2013;Flores et al, 2014). En el presente trabajo se realiza un análisis macroscópico y microscópico de las gónadas de hembras de Anadara tuberculosa de la localidad de Bajo Alto, Provincia de El Oro.…”
Section: Palabras Clave 589unclassified
“…Los resultados obtenidos en este estudio preliminar, demuestran que los organismos analizados se encuentran en actividad reproductiva, particularmente en los procesos vitelogenicos y madurez final de los ovocitos tal como se evidencia en los cortes histológicos (Figura 1), donde se visualiza los folículos con ovocitos maduros y núcleo bien definidos y en menor grado, algunos aún no tan desarrollados. Estos resultados concuerdan con los períodos reproductivos señalados para esta especie en las costas del Ecuador (Ayala et al, 2013;Flores et al, 2014). Pudiendo suponer que estos meses se corresponden con un período de máxima maduración.…”
Section: Análisis Histológicounclassified